2021
DOI: 10.18203/2320-1770.ijrcog20215099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transvaginal sacrospinous ligament fixation with abdominal sacrocolpopexy in treatment of post-hysterectomy vault prolapse-a prospective randomized study

Abstract: Background: Vaginal vault prolapse is a common condition following abdominal or vaginal hysterectomy causing negative impact on women’s quality of life. The study compares the efficacy of abdominal and vaginal route surgery in correcting post-hysterectomy vault prolapse by postoperative assessment and at least twelve months follow up.Methods: A prospective comparative study among post-hysterectomy patients attending the GOPD of Midnapore Medical College diagnosed as vaginal vault prolapse at least stage2 betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Clinically, the right sacrospinous ligament is believed to be more easily accessible during sacrospinous fixation by righthanded surgeons. 18 This preference may account for the disproportionate 'failure' of the right mesh arm (potentially due to asymmetrical tensioning and subsequent gradual lengthening) that leads to a laterally displaced upper vagina towards the patient's left side. Additionally, it was found that with hysterectomy, a lower vaginal position was associated with prolapse recurrence-which aligns with previous studies that demonstrated that the vagina of women with POP versus without POP was positioned lower within the 19,20 Our findings also showed that among successes, hysteropexy was better able to preserve a more horizontally and posteriorly oriented upper vagina than hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, the right sacrospinous ligament is believed to be more easily accessible during sacrospinous fixation by righthanded surgeons. 18 This preference may account for the disproportionate 'failure' of the right mesh arm (potentially due to asymmetrical tensioning and subsequent gradual lengthening) that leads to a laterally displaced upper vagina towards the patient's left side. Additionally, it was found that with hysterectomy, a lower vaginal position was associated with prolapse recurrence-which aligns with previous studies that demonstrated that the vagina of women with POP versus without POP was positioned lower within the 19,20 Our findings also showed that among successes, hysteropexy was better able to preserve a more horizontally and posteriorly oriented upper vagina than hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the right mesh arm appeared loose and wave‐like compared with the left mesh arm on MRI, suggesting consistent asymmetrical loss of support. Clinically, the right sacrospinous ligament is believed to be more easily accessible during sacrospinous fixation by right‐handed surgeons 18 . This preference may account for the disproportionate ‘failure’ of the right mesh arm (potentially due to asymmetrical tensioning and subsequent gradual lengthening) that leads to a laterally displaced upper vagina towards the patient's left side.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal eversion is essentially complete. For SSF: SSF is done classically as described by Randall et al 3 Vertical incision is given on anterior vaginal wall, vault and posterior vaginal wall. Dissection was carried out up to right sided ischial spine in pararectal space after dividing rectal pillar and rectum is mobilized away from site and curved needle was passed through right sacrospinous ligament about 2-3 cm medial to ischial spine by palpating the ligament.…”
Section: Stagementioning
confidence: 99%